2016
DOI: 10.7717/peerj.2097
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of immature xylem in the Chinese fir at different developmental phases

Abstract: Background.Chinese fir [Cunninghamia lanceolata (Lamb.) Hook.] is one of the most important native tree species for timber production in southern China. An understanding of overall fast growing stage, stem growth stage and senescence stage cambium transcriptome variation is lacking. We used transcriptome sequencing to identify the repertoire of genes expressed during development of xylem tissue in Chinese fir, aiming to delineate the molecular mechanisms of wood formation. Results. We carried out transcriptome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
16
1
1
Order By: Relevance
“…The molecular aspects of the effects of age on wood formation in trees have been studied, and different classes of genes controlling wood formation have been revealed (Li et al 2010Xu et al 2016;Zhang et al 2016). Especially, using cryosectioning and RNA-Seq methods, Xu et al (2016) compared the transcriptome of vascular cambium tissue in Cunninghamia lanceolata at juvenile, transitional, and mature stages to study the effects of age on cambium activity.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular aspects of the effects of age on wood formation in trees have been studied, and different classes of genes controlling wood formation have been revealed (Li et al 2010Xu et al 2016;Zhang et al 2016). Especially, using cryosectioning and RNA-Seq methods, Xu et al (2016) compared the transcriptome of vascular cambium tissue in Cunninghamia lanceolata at juvenile, transitional, and mature stages to study the effects of age on cambium activity.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…In studies of the molecular mechanisms of tree aging, many age-related genes have been identified (Busov et al 2004;Carlsbecker et al 2004;Diego et al 2004;Fernández-Ocaña et al 2010;García-López et al 2014;Hutchison et al 1990;Li et al 2010Xu et al 2016;Zhang et al 2016), such as miR156 (Wang et al 2011b) and Flowering Locus T (Böhlenius et al 2006;Hsu et al 2006Hsu et al , 2011, and some have been used to change the agronomic traits of plants (Flachowsky et al 2012;Kotoda et al 2006;Li et al 2013a;Yamagishi et al 2014). Larix kaempferi is a forest tree of important ecological and economic value, widely grown in the Northern Hemisphere, but its genome has not been sequenced.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…This feature makes it more attractive for conifer tree breeders to adopt the high-throughput sequencing (HTS) platform as a straightforward tool in their molecular breeding program.Chinese fir (Cunninghamia lanceolata) is one of the major commercial conifer species in China. It covers~21.4% of man-made plantations and supplies up to 20%-30% of the total commercial timber production of China [19,20]. Highly valued for timber and essential ecosystem services this conifer has been used as a major breeding subject of the tree improvement programs of China for over 50 years [21].…”
mentioning
confidence: 99%
“…In the present study, 85 PeMYBs were identified in moso bamboo, and the number of PeMYB members was slightly less than that found in other monocotyledonous and dicotyledonous plants (Dubos et al, 2010;Li et al, 2016c;Zhang et al, 2016). It is likely that the bamboo genome is a draft, which does not cover the entire genome (Peng et al, 2013).…”
Section: Homology Of Gene Structure Indicated Close Evolutionary Relamentioning
confidence: 56%
“…Diametrically, the amino acid sequence outside of the DNAbinding domain, the C-terminus, is an activated structure that is highly divergent in length and sequence, which gives rise to the functional diversity of the MYB proteins (Kranz, Scholz & Weisshaar, 2000;Jin & Martin, 1999). Based on the number of repeats, the MYB family is classified into four subfamilies, namely, 1R-MYB (MYB-related), 2R-MYB (R2R3-MYB), 3R-MYB (R1R2R3-MYB) and 4R-MYB (Dubos et al, 2010;He et al 2016). In plants, R2R3-MYB are the largest and most common MYB TFs (Dubos et al, 2010;Du et al, 2013;Niu, Jiang & Xu, PeerJ reviewing PDF | (2018:08:30682:2:1:NEW 7 Dec 2018)…”
Section: Introductionmentioning
confidence: 99%